Sport and exercise as risk factors for eating disorders - Plateau, C. R.; Arcelus, J. (Eating Disorders, 2023)
A persistent drive to exercise has been widely recognized as a salient presenting feature of eating disorder (ED) psychopathology. Establishing potential mechanisms by which exercise may contribute toward the onset and trajectory of eating psychopathology has therefore been an important focus of research. Evidence suggests that cognitions about, and motivations for exercise are critical in driving links with eating psychopathology; specifically, exercise that is compulsive, rigid, and driven by motivations to adjust weight/shape and to manage negative affect has been linked to an increased risk and severity of eating psychopathology. Notably, ED psychopathology is more prevalent in exercising populations (e.g., elite athletes, dancers). The enhanced focus on weight and shape (e.g., via weight monitoring, critical comments, comparison with peers and requirements to wear revealing clothing) in the sports and dance context may contribute toward the development of eating psychopathology in athletes. However, differentiating normative from problematic eating and exercise behaviors in athletes, including dancers, is challenging. Identifying athletes and dancers with compulsive exercise attitudes and behaviors may offer a potential means by which to distinguish those at an increased risk of eating psychopathology. Furthermore, providing sports personnel with training and education about EDs may facilitate earlier signposting of athletes to treatment and support.